Social support within a mother and child group: An ethnographic study situated in the UK. (24th January 2013) - Peters, Jane; Skirton, Heather
Abstract Social support has been associated with positive outcomes regarding the mothering experience, and professional interventions have therefore been developed in formal settings to promote this. An ethnographic approach was used to consider the subjective experiences of mothers attending a professionally‐facilitated group for parents and children aged 0–4 years, focusing on relationships within the group and their importance within existing social networks. Qualitative data were collected from seven participants using interviews and participant observation. These were analyzed by the constant comparison method into codes, categories, and themes. Three themes emerged: past history, being a mother, and function of the group. To ensure mothers and children benefit from such groups, nurses who participate in developing and leading community interventions for mothers and their children need to be aware of the importance of maternal identity and the factors that can impact the relationships between mothers within group settings.